2019
DOI: 10.1101/710913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The plasmid diversity ofAcinetobacter bereziniaeHPC229 provides clues on the ability of the species to thrive on both clinical and environmental habitats

Abstract: AbstractAcinetobacter bereziniae is an environmental microorganism with increasing clinical incidence, and may thus provide a model for a bacterial species bridging the gap between the environment and the clinical setting. A. bereziniae plasmids have been poorly studied, and their characterization could offer clues on the causes underlying the leap between these two radically different habitats. Here we characterized the who… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…These inferences indicated that Rep_3 plasmids carrying pXerC/D-bounded genes were already present in the A. baumannii population before the massive anthropogenic introduction of antimicrobials by the middle of last century (Antunes et al, 2014;Baquero et al, 2021). GGTGTA cr sequences can also be found among 6 out of the 17 non-identical pXerC/D sites identified by us among Ab242/Ab825 plasmids (Cameranesi et al, 2018), and between many of the multiple pXerC/D sites described in other plasmids of many Acinetobacter (and even non-Acinetobacter) strains isolated in different periods and from different sources, both clinical and environmental (Fu et al, 2014;Blackwell and Hall, 2017;Brovedan et al, 2019;Matos et al, 2019;Mindlin et al, 2019;Balalovski and Grainge, 2020;Bonnin et al, 2020;Salgado-Camargo et al, 2020;Wang et al, 2020;Alattraqchi et al, 2021;Hamidian et al, 2021;Liu et al, 2021;Jones et al, 2022). Although it remains to be established what other factors influence the feasibility (or reversibility) of SSR events between sites sharing identical cr sequences, it is likely that some of these sites participate in the remodeling and evolution of Acinetobacter plasmids in the eventuality that they collide in the same cell, with the concomitant accelerated dissemination of the resistance determinants they bound.…”
Section: Discussionmentioning
confidence: 77%
“…These inferences indicated that Rep_3 plasmids carrying pXerC/D-bounded genes were already present in the A. baumannii population before the massive anthropogenic introduction of antimicrobials by the middle of last century (Antunes et al, 2014;Baquero et al, 2021). GGTGTA cr sequences can also be found among 6 out of the 17 non-identical pXerC/D sites identified by us among Ab242/Ab825 plasmids (Cameranesi et al, 2018), and between many of the multiple pXerC/D sites described in other plasmids of many Acinetobacter (and even non-Acinetobacter) strains isolated in different periods and from different sources, both clinical and environmental (Fu et al, 2014;Blackwell and Hall, 2017;Brovedan et al, 2019;Matos et al, 2019;Mindlin et al, 2019;Balalovski and Grainge, 2020;Bonnin et al, 2020;Salgado-Camargo et al, 2020;Wang et al, 2020;Alattraqchi et al, 2021;Hamidian et al, 2021;Liu et al, 2021;Jones et al, 2022). Although it remains to be established what other factors influence the feasibility (or reversibility) of SSR events between sites sharing identical cr sequences, it is likely that some of these sites participate in the remodeling and evolution of Acinetobacter plasmids in the eventuality that they collide in the same cell, with the concomitant accelerated dissemination of the resistance determinants they bound.…”
Section: Discussionmentioning
confidence: 77%
“…These authors suggested that the presence of plasmids is one of the sources of genetic diversity and that frequently, heavy metal resistance in acinetobacters is plasmid encoded [57]. Other researchers also showed multiple plasmids (plasmidome) encoding resistance to Hg, Cr, Co/ Zn/Cd, Ni, and As in Acinetobcter strains and suggested that these plasmidomes can provide resistance to heavy metals in both environmental and clinical habitats [58][59][60]. El-Sayed [61] determined dual expressions of heavy metal and antibiotic resistance from A. baumannii strain HAF-13, a potential seed for decommissioning of sites polluted with industrial effluents rich in heavy metals, since this isolate will be able to withstand in situ antibiosis that may prevail in such ecosystems.…”
Section: Plos Onementioning
confidence: 99%